The Urgency of Education in Islamic Boarding Schools in Improving The Quality of Islamic-Based Character Education - Fauzi, Irzhal; Hosna, Rofiatu (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2022)
This research aims to determine the importance of education at the Miftahul Mubtadiin Ar-Ridlo Islamic Boarding School, Nganjuk, in increasing the quality of Islamic character education. A qualitative approach is used in this study. Researchers employed observation techniques, interviews, and documentation to obtain data. According to the findings of this study, character education at the Miftahul Mubtadiin Ar-Ridlo Islamic Boarding School, Nganjuk, is well maintained and operational. It is demonstrated by alumni who have good personalities, noble character, and the ability to live independently. Supporting variables include students, caregivers and caregivers who persevere, and families that consistently provide good direction and habituation to students during vacations (in particular). The problems found are personal factors, environmental factors and the rapid development of science and technology. So it can be concluded the character education in pesantren can be effective with the coaching, mentoring, and unique approaches by ustadz and administrators, parents and banning electronic devices. According to the existing description, education at the Miftahul Mubtadiin Ar-Ridlo Islamic Boarding School, Nganjuk, substantially boosts the quality of Islamic character education.